Geometrical Insights of Transient Diffusion Layers - Molina, A; Gonzalez, J; Martinez-Ortiz, F; Compton, R (2010)
Very simple explicit expressions for the diffusion layer thicknesses (δl) under transient conditions have been deduced for different geometries of the diffusion field. From these expressions we have completely quantified and characterized the variation of δl in normal pulse voltammetry, staircase voltammetry, and linear sweep voltammetry at planar, cylindrical, and spherical electrodes of any size. The influence of the time duration, the potential, the sweep rate, and the electrode radius has been analyzed, and interesting limit expressions for δl corresponding to E. E0 and E, E0 have also been deduced. The conditions required to attain stationary state are given. © 2010 American Chemical Society.